Proceedings of the Asia Pacific Business and Economics Conference (APBEC 2018) 2019
DOI: 10.2991/apbec-18.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Employees’ Views on Fraud Awareness and Anti-Fraud Strategy

Abstract: The purpose of this study is to analyze the implementation of an anti-fraud strategy and to find out the level of fraud awareness of employees in PT XYZ, one of the selfregulatory organization in Indonesia. The focus of this study is the implementation of fraud prevention, detection, and response strategies in PT XYZ, and analyzing employees' perceptions on the motivating factors of fraud and implementation of anti-fraud strategy in the company as part of fraud awareness. Findings show that PT XYZ has been imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Various surveys on fraud have revealed that a whistleblowing system and internal company management play a vital role in supporting the growth of integrity and good corporate governance. Implementing a whistleblowing system not only promotes internal transparency but also provides protection and encourages employees to report fraudulent practices, thereby aiding in the early detection and prevention of fraud (Astriana & Adhariani, 2019;Nwakeze et al, 2023). In Indonesia, although the concept of a whistleblowing system is relatively new, awareness of its existence and importance continues to grow among companies, both private and government-owned, such as WIKA, Bank Indonesia, Sinar Mas, and Pertamina, demonstrating its effectiveness in maintaining workplace safety and protecting company profits and reputation (Meiryani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Various surveys on fraud have revealed that a whistleblowing system and internal company management play a vital role in supporting the growth of integrity and good corporate governance. Implementing a whistleblowing system not only promotes internal transparency but also provides protection and encourages employees to report fraudulent practices, thereby aiding in the early detection and prevention of fraud (Astriana & Adhariani, 2019;Nwakeze et al, 2023). In Indonesia, although the concept of a whistleblowing system is relatively new, awareness of its existence and importance continues to grow among companies, both private and government-owned, such as WIKA, Bank Indonesia, Sinar Mas, and Pertamina, demonstrating its effectiveness in maintaining workplace safety and protecting company profits and reputation (Meiryani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Sebagai salah satu strategi pengurangan fraud yang dianjurkan untuk dilakukan, strategi anti fraud terdiri dari 4 (empat) pilar yaitu pencegahan; deteksi; investigasi, pelaporan, dan sanksi; serta pemantauan, evaluasi, dan tindak lanjut yang sesuai dengan ketentuan Peraturan Otoritas Jasa Keuangan Nomor 39/POJK.03/2019 (Otoritas Jasa Keuangan, 2019). Namun beberapa penelitian mengenai strategi anti fraud yang sudah dilakukan oleh peneliti sebelumnya [Astriana & Adhariani (2019); Murti & Kurniawan (2020); Roemkenya & Bayunitri (2021);Agustina et al (2021); dan Aziz & Othman (2021)] hanya mengangkat salah satu pilar atau beberapa pilar strategi saja. Penelitian mengenai strategi anti fraud yang langsung membahas keempat pilar tersebut dalam satu penelitian belum banyak dibahas.…”
unclassified